Countering Far-Right Anti-Government Extremism in the United States - Robinson, Kaitlyn (Perspectives on terrorism, 2023)
The far-right anti-government extremist movement poses a significant threat in the United States. The January 6, 2021, attack on the US Capitol illustrates the capacity of this movement to plan and mount violent attacks against government targets and democratic institutions. In this article, we explore how the organisational and tactical characteristics of the far-right anti-government movement in the United States enable it to thrive despite the dangers it poses to the public. We argue that its deep-seated ideological roots, fluid organisational structure, and mix of violent and nonviolent tactics make the movement difficult for federal and state authorities to proscribe, prosecute, and ultimately eliminate. US policymakers need to develop an informed response that accounts for the fluid, decentralised, and public-facing nature of anti-government extremism, as well as the pervasive distrust of federal authority that it reflects. We suggest that this approach will likely differ from the modern counter-terrorism tools that were initially designed to combat terrorist threats emanating from abroad, such as those posed by Al Qaeda and the Islamic State. We ground our arguments in evidence from cases of anti-government extremist groups and followers active in the United States over the past three decades.